Suicide and the Gothic - Hughes, William, 1964-; Smith, Andrew, 1964- (Manchester University Press, 2019)
'Suicide and the Gothic is the first protracted study of how the act of self-destruction recurs and functions within one of the most enduring and popular forms of fiction. Comprising eleven original essays and an authoritative introduction, this collection explores how the act of suicide has been portrayed, interrogated and pathologised from the eighteenth century to the present. The featured fictions embrace both canonical and the less-studied texts and examine the crisis of suicide - a crisis that has personal, familial, religious, legal and medical implications - in European, American and Asian contexts. Featuring detailed interventions into the understanding of texts as temporally distant as Thomas Percy's Reliques and Patricia Highsmith's crime fictions, and movements as diverse as Wertherism, Romanticism and fin-de-siècle decadence, Suicide and the Gothic provides a comprehensive and compelling overview of this recurrent crisis in fiction and culture' --Publisher.
Made available via: manchesterhive.
Keywords: Gothic fiction (Literary genre), English -- History and criticism.; Suicide in literature.; Suicide dans la littérature.; Literature and literary studies.; LITERARY CRITICISM -- General.; LITERARY CRITICISM / General; Suicide in literature; Gothic fiction (Literary genre), English; Gothic.; Romanticism.; crime fiction.; eighteenth century.; fin de siècle.; literature.; nineteenth century.; suicide.; twentieth century.; Electronic books; Criticism, interpretation, etc.